2019
DOI: 10.1097/md.0000000000015737
|View full text |Cite
|
Sign up to set email alerts
|

Solitary fibrous tumor of the pineal region with delayed ectopic intracranial metastasis: A case report and review of the literature

Abstract: Rationale: Solitary fibrous tumors of central nervous system are rare spindle-cell mesenchymal tumors. Although most are benign in nature, malignant transformation and extracranial metastasis have been reported. Up to now, only one case of CSF dissemination was described. Here we described an extremely rare case of intracranial Solitary fibrous tumors arising from the pineal region with a delayed ectopic metastasis. Patient concerns: A 35-year-old female presented with … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
5
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(6 citation statements)
references
References 38 publications
1
5
0
Order By: Relevance
“…CNS SFTs are most commonly located along the falx cerebri, occipital and spinal dura, tentorium cerebelli, and at the cerebellopontine angle, and often have an attachment to the meninges [4] . However, SFTs in the pineal region are rare, with only five cases, including the present case, being reported to date [3] .…”
Section: Discussionmentioning
confidence: 68%
See 1 more Smart Citation
“…CNS SFTs are most commonly located along the falx cerebri, occipital and spinal dura, tentorium cerebelli, and at the cerebellopontine angle, and often have an attachment to the meninges [4] . However, SFTs in the pineal region are rare, with only five cases, including the present case, being reported to date [3] .…”
Section: Discussionmentioning
confidence: 68%
“…Intracranial SFTs occur at a median age of 42.5 years, and rarely in individuals as old as 80 years [2] . CNS SFTs are most commonly located along the falx cerebri, occipital and spinal dura, tentorium cerebelli, and at the cerebellopontine angle, with only a few cases reports involving the pineal region [3] , [4] . We herein present a case of SFT in the pineal region of an 80-year-old man and review the literature.…”
Section: Introductionmentioning
confidence: 99%
“…There are studies advocating that RT is not strictly indicated after complete resection due to close follow-up and low recurrence rate [4] and that adjuvant radiotherapy can be considered in the case of subtotal resection [26][27][28] or if we are facing a high grade SFT [29]. There are studies advocating adjuvant radiotherapy be standard of treatment [18,30].…”
Section: Discussionmentioning
confidence: 99%
“…An additional lesion that was considered in the differential diagnosis was a solitary fibrous tumor (SFT), which are rare spindle cell mesenchymal tumors [23]. The confirmation of this diagnosis is based on a positive result for CD34 and a negative result for S100 protein staining in immunohistochemistry [24].…”
Section: The Histopathological Differential Diagnosismentioning
confidence: 99%